Development of human-robot interaction (HRI) methodology for autism rehabilitation using humanoid robot with a telerehabilitation platform / Syamimi Shamsuddin - Shamsuddin, Syamimi (Institute of Graduate Studies, UiTM, 2016)
Advances in technologies and improvements in diagnostic procedures have contributed to the rising number of autism detection worldwide. Autism is a brain disorder that affects behaviour, communication and social interaction. The use of intelligent robots to rehabilitate children with autism hosts great untapped potential. Robots offer rehabilitation applications that are accurate, motivating and repetitive. However, validity and access to such intervention are still scarce. This research investigates the potential use of a humanoid robot as an adjunct rehabilitation tool to assist children with autism. The focus is also on developing a single, web-based platform that enables stakeholders in autism rehabilitation to gain access to robotic applications. A robot in human shape has great potential to generalize the skills learnt during humanrobot interaction to human-human interaction scenarios. The humanoid robot used in this study is NAO. It has moderate degree of likeness to human. Children with autism prefer robots with simplified features. NAO is also the most widely used humanoid platform by engineering and clinical researchers in autism research. The first objective analyses the behaviour response of children with autism when exposed to a humanoid robot for the first time. The pilot experiment took place at NASOM Titiwangsa, a special school for children with autism. A 24-items behaviour score sheet was developed as an observation instrument to measure the children’s responses. Qualitative results from video evaluations showed that for the subscale of stereotyped behaviour and communication, 10 children responded positively with reduced autistic behaviour when the robot was present…